2021
DOI: 10.1037/pst0000342
|View full text |Cite
|
Sign up to set email alerts
|

A clinical practice review of crying research.

Abstract: The goal of this clinical practice review is to assess the current state of the theoretical and empirical literature on emotional crying (i.e., crying in response to an emotional stimulus), a topic that has received surprisingly limited attention of behavioral scientists and clinicians. Although the empirical research on emotional crying remains in a nascent state, we draw upon the existing scientific knowledge to provide preliminary suggestions for clinicians on how to interpret and respond to crying in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 109 publications
(208 reference statements)
0
16
0
Order By: Relevance
“…Depressed individuals also show alterations in their crying behavior, such as increases in crying frequency, although decreases in the ability to cry have also been observed at more severe levels of depression (Rottenberg et al., 2008). Crying has also been long considered an important focus of psychotherapy that may facilitate emotional processing, attachment, and interpersonal functioning (Bylsma, Gračanin, et al., 2020); however, little is known about how crying changes with the course of depression or in response to intervention.…”
Section: Characterization Of Within and Cross‐level Interactions Acromentioning
confidence: 99%
“…Depressed individuals also show alterations in their crying behavior, such as increases in crying frequency, although decreases in the ability to cry have also been observed at more severe levels of depression (Rottenberg et al., 2008). Crying has also been long considered an important focus of psychotherapy that may facilitate emotional processing, attachment, and interpersonal functioning (Bylsma, Gračanin, et al., 2020); however, little is known about how crying changes with the course of depression or in response to intervention.…”
Section: Characterization Of Within and Cross‐level Interactions Acromentioning
confidence: 99%
“…As the field of psychotherapy research progressed, there has been a shift from viewing crying in therapy primarily as having strictly a cathartic value, to a broader perspective emphasising additional effects of crying in therapy, such as its role in insight gained in treatment as well as its relation with the therapeutic alliance (Bylsma et al, 2021; Genova et al, 2020; Nelson, 2007; Zingaretti et al, 2017). It has been suggested that the relationship between crying and the therapeutic alliance can be both positive and negative, depending on the context.…”
Section: Introductionmentioning
confidence: 99%
“…Crying frequently accompanies a variety of emotional situations (e.g., relational conflict, perceived personal failure and loss) and can convey important and clinically useful information about the relationships and situations that matter to the patient (Beck et al, 1979). Different theoretical orientations diverge in what they underscore as the most noteworthy aspects of crying: for example, emotional expression and catharsis in psychodynamic theory, social context and communicative function of crying in interpersonal approaches, and cognitive appraisals in CBT approaches (Bylsma et al, 2020). However, in spite of their differences, there seems to be consensus among the major paradigms that crying in therapy presents unique opportunities for patients to engage in affective experiences and explore their meaning.…”
Section: Introductionmentioning
confidence: 99%
“…Psychotherapy can be a highly emotional process. It is thus not surprising that crying is a common occurrence in this setting (Robinson et al, 2015; Trezza et al, 1988; Zingaretti et al, 2017), with estimates suggesting at least one crying episode in 15–30% of therapy sessions (Bylsma et al, 2020). Crying frequently accompanies a variety of emotional situations (e.g., relational conflict, perceived personal failure and loss) and can convey important and clinically useful information about the relationships and situations that matter to the patient (Beck et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation